Pelaksanaan Pembiayaan Murabahah Pada Spp Pnpm-Mp Menurut Tinjauan Ekonomi Syariah - Hidayatina, Hidayatina; Suriani, Suriani (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2023)
The aim of this research are: 1) to know the implementation of the business capital assistance program for SPP PNPM-MP in Tanjong Pineung Village, Seunuddon District, North Aceh Regency Subdistrict) 2) to know the sharia economy review on the implementation of capital assistance program for SPP PNPM-MP in Tanjong Pineung Village, Seunuddon District, North Aceh Regency subdistrict. This research is qualitative research. The results of this research are: the implementation of business capital assistance for SPP PNPM-MP in Tanjong Pineung Village, Seunuddon District, North Aceh Regency, sub-district using murabaha system in the form of gold in accordance with the amount in accordance with the granted by the UPK SPP PMPM-Mandiri management in Gampong Murong Samudra District, and the concept of SPP financing carried out in Tanjong Pineung Village, Seunuddon District is still not in accordance with Islamic economics. This is evident in the implementation which is still the same as the previous concept, namely the percentage of interest. The murabahah contract referred to as sharia principles applied in the management of business capital assistance SPP PNMP-MP still seems only as a symbol, while in practice it has not been based on Islamic legal provisions, specifically the provisions of the murabahah contract.